Impacts of enrichment programs on cognitive and affective skills of gifted students: A meta-analysis - M. Davut Gül; Zekai Ayık (PLoS ONE, 2025)
This meta-analysis aims to study research on enrichment programs for gifted students and synthesize the effects on cognitive and affective skills reported by studies conducted between 2014–2024 years. During the screening process, the focus was on quantitative studies published between 2014 and 2024 that explored the influence of enrichment programs (ER) on cognitive and affective abilities of gifted students. Searches were carried out in Web of Science and Scopus databases for publications in English. The researchers examined publication bias by analysing data using various methods, including the funnel plot, Begg’s test, Egger’s test, and trim-and-fill test. Additionally, the researchers utilized Classic fail-safe N and Orwin’s fail-safe N values for further analysis. Hedges’s g was used to report the magnitude or strength of the standardized mean differences between groups in a study as effect size, since it provides effect size for smaller sample sizes. A total of 16 publications included in this meta-analysis, and results demonstrated that enrichment programs had a large effect on cognitive skills (g = 1.14, 95% CI [.83, 1.45], under random-effect model), a medium effect on affective personal skills (g = .51, 95% CI [.30,.73], under random-effect model), and small impact on affective social skills (g = .44, 95% CI [.23,.66], under random-effect model). This review underscores nuanced findings focusing on sub-domains of achievement, higher-order thinking, and personal and social-affective skills. The overall results implied that enrichment programs play a significant role in fulfilling both the cognitive and non-cognitive needs of gifted students.